Digital transformation in financial sector - Iriskulov Temur Xayrulla ogli (Periodica Journal, 2023)
Digital transformation is a necessity for banks. Changes in consumer needs, along with the need to reduce costs and increase efficiency, leave banks with no other option but to change and use modern technologies. But these changes carry risks with them. Banks need to have sustainable business models to be ready for them
Keywords: transformation; sustainable; business; ready